Culturological dimensions of artistic image - M. M. Brovko (Ukrainian Cultural Studies, 2017)
Research of the cultural artistic image is the issue of the nowadays of contemporary aesthetics. As a result, of that value that is acquired by artistic images in a modern culture, and new creative opportunities of cultural development, in the sphere of arts that is predefined by new realities in the field of cultural existence of man in the world. In Ukrainian scienctific research withstand and accept thesis the point that art, mainly in the formof image, becomes active, culturecreative force that acts directly on spiritual-emotional world of a person. At the sametime, culture-creative activity of art can appear beyond and pose vivid embodiment of artistic idea. A work of art is able to reflect theoretical, moral, legal and other public ideas that can influence on people exactly in such their hypostasis. To a large extent relying on modern, and not only modern, artistic practice, and taking into account theoretical works, we can confidently talk about the levels of vividness of art and levels of activity, cultural-creative nature of art. An important moment in terms of clarifying the cultural specificity of the artistic image is that it, thanks to its content, is constantly included in the structure of social practice. In order to outline the way of analyzing the artistic image as a special phenomenon of culture the essential features of which are expressed in its cultural potential, it is firstly necessary to understand what the image represents an integral cultural and spiritual formation that has certain properties and qualities distinguishing it from all other spiritual phenomena. It is necessary to clarify the structural and typological features, which, on the one hand, characterize it as a specific element of art, and on the other – contain something that constantly displays the artistic image beyond the boundaries of art. The concept of the "image-action" is able to grasp by its content a number of artistic features that characterize it, on the one hand, as a way of spiritual and practical mastering by a person of reality in accordance with all the consequences that stem from this feature of art. With the other – with the possibilities of analysis open from the standpoint of its active being in society as a phenomenon of culture, its cultural dimensions.